Budgeting in Denmark - Blöndal, Jón R.. (OECD Publishing, 2006)
Denmark has a very large public sector and this has historically been the case. Currently at over 56% of GDP, the size of the public sector in Denmark is larger than that of any other OECD member country except Sweden